2015
DOI: 10.1016/j.schres.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Validation of mismatch negativity and P3a for use in multi-site studies of schizophrenia: Characterization of demographic, clinical, cognitive, and functional correlates in COGS-2

Abstract: Mismatch negativity (MMN) and P3a are auditory event-related potential (ERP) components that show robust deficits in schizophrenia (SZ) patients and exhibit qualities of endophenotypes, including substantial heritability, test-retest reliability, and trait-like stability. These measures also fulfill criteria for use as cognition and function-linked biomarkers in outcome studies, but have not yet been validated for use in large-scale multi-site clinical studies. This study tested the feasibility of adding MMN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 77 publications
10
130
1
6
Order By: Relevance
“…In line with this, pharmacological studies suggest MMN reflects glutamatergic processes [60,61], whereas P3a amplitude is modulated by dopamine (and hence current anti-psychotic medications) [62,63]. Consistent with the findings for MMN, P3a amplitude correlates with cognitive and psychosocial functioning [59,64,65], and is reduced in schizophrenia [59,66], first episode psychosis [37, 41,64,67], and in at risk samples [36,37,39,41]. Thus P3a might provide an additional biomarker for psychosis but targeting different disease processes, and can be readily measured concurrently with MMN.…”
Section: The P3asupporting
confidence: 67%
See 2 more Smart Citations
“…In line with this, pharmacological studies suggest MMN reflects glutamatergic processes [60,61], whereas P3a amplitude is modulated by dopamine (and hence current anti-psychotic medications) [62,63]. Consistent with the findings for MMN, P3a amplitude correlates with cognitive and psychosocial functioning [59,64,65], and is reduced in schizophrenia [59,66], first episode psychosis [37, 41,64,67], and in at risk samples [36,37,39,41]. Thus P3a might provide an additional biomarker for psychosis but targeting different disease processes, and can be readily measured concurrently with MMN.…”
Section: The P3asupporting
confidence: 67%
“…MMN and P3a amplitude increased and latency decreased with age most likely due to maturational changes during the teenage years. Other studies in healthy adolescents have found similar age effects for frequency MMN [110,111], but in older age groups there are consistent reports of MMN amplitude reductions with age [29,59] with maximal amplitudes seen in 20-30 year old adults. Within the UHR literature, age effects have been poorly reported, but some studies have reported adjusted MMN effects assuming a linear relationship between age and MMN amplitude [33, 41,43].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…To this end, we recently found that the auditory mismatch negativity and later peak features of responses to unattended auditory oddball stimuli predict response to initial exposure to auditory training and are sensitive and early indices of sensory "engagement." We can envision a future in which EEG information in conjunction with other demographic, clinical, and genetic predictors may be used both to improve the identification of individuals at clinical risk for developing psychosis and to inform assignment of interventions that are most likely to provide therapeutic benefits (6,8,11).…”
Section: Eeg Biomarkers For Treatment Selectionmentioning
confidence: 99%
“…Beyond the substantial validation required for large-scale deployment, instrumentation will need to be simplified to allow administration by nonspecialists in real-world community treatment centers. To this end, the Consortium on the Genetics of Schizophrenia recently demonstrated that neural responses to deviant auditory oddball stimuli can be reliably measured in settings without extensive technician training or expertise in EEG assessment and analysis (11). Such ready "scalability" should also be a development goal for studies using future, more sensitive, source-resolved EEG biomarkers.…”
Section: Using Eeg Biomarkers In Clinical Carementioning
confidence: 99%